Implementation of the Kribo Sinando Method to Increase the Critical Reasoning Dimension in Indonesian Language Learning in Elementary Schools - Sutarti,; Setianti, Tutun Finfin; Cahyo Khosiyono, Banuh Havivah; Al Masjid, Akbar (International Conference on Elementary Education, 2025)
This research raises the problem of how to improve critical reasoning skills using the KRIBO SINANDO method (Kritik Bahasa Obrolan Sinema Anak Indonesia). The research purpose is to describe the improvement of students' critical reasoning skills in learning Indonesian, especially in the material on the use of effective sentences. This research method uses a case study approach in the form of a one-shot case study. The subjects in this study are 28 students in grade VI of SD Negeri Demakijo 2. The research was carried out by providing actions in the form of applying the Kribo Sinando method and after that observations, interviews, and documentation of student learning outcomes were carried out. The results of the implementation showed that there was an increase in student learning outcomes from the initial condition and after the implementation of Kribo Sinando in the initial condition, students. With the use of the Kribo Sinando method, there was an increase in the completeness of learning outcomes from the conditions before the use of the Kribo Sinando method (60.71%) and after applying this method, the achievement of learning completeness was 100%. Another result of this implementation is the creation of more active, inclusive, and fun learning for students. The results of the study can conclude that the use of the Kribo Sinando Method can improve students' critical reasoning skills in learning Indonesian in grade VI students of SD Negeri Demakijo 2.